Development of the Japanese version of the Cornell Assessment of Pediatric Delirium. Issue 1 (3rd October 2017) - Hoshino, Haruhiko; Matsuishi, Yujiro; Shimojo, Nobutake; Enomoto, Yuki; Kido, Takahiro; Inoue, Yoshiaki
Abstract : Aim: Delirium is a form of acute cerebral dysfunction and is associated with increased length of hospital stay, mortality, and health‐care costs for adult patients in intensive care. However, in Japan, there are currently no reliable criteria or tools for diagnosing delirium in critically ill pediatric patients. The purpose of this study was to translate the Cornell Assessment of Pediatric Delirium (CAPD)—a screening tool for pediatric delirium—from English to Japanese for use in the diagnosis of delirium for pediatric patients in pediatric intensive care units. Methods: The back‐translation method was used to ensure equivalence in the Japanese version of the CAPD and its accompanying developmental anchor points. The translation process was repeated by a multidisciplinary committee of medical researchers and clinicians. Results: The final back‐translated version of the CAPD was submitted to the original author, who gave her approval. Conclusion: The Japanese CAPD was developed and its effectiveness tested using a standardized procedure. Further study is required to test the validity and reliability of the Japanese version of the CAPD. Abstract : This study investigated Japanese version of CAPD which is delirium screening tool in pediatric intensive care unit. We developed Japanese version of CAPD to use back translation method.